Inovasi Mi Basah Menggunakan Tepung Mocaf Dengan Penambahan Puree Labu Kuning - Gadis Rizkynia Aisya; Lilis Sulandari; Ita Fatkhur Romadhoni; Andika Kuncoro Widagdo (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Wet noodles are raw noodles that are boiled in boiling water before being marketed. The making of noodles includes the stages of mixing, forming cutting sheets or printing and cooking. The average yellow noodles that are often sold in the market are dry noodles, wet noodles that are traded on average white noodles. In this report, the researcher wants to make an innovation of yellow wet noodles. The type of additional ingredient in wet noodles that functions to give a natural yellow color is yellow pumpkin. The nutritional content of yellow pumpkin is quite large, including rich in vitamins A & C, minerals, and carbohydrates, and the flesh of yellow pumpkin also contains antioxidants that are useful as anti-cancer. The addition of this yellow pumpkin will make wet noodles rich in β-carotene and can improve the color of processed products. This study used a pattern design of yellow pumpkin puree addition factor with 3 treatments, namely (30 grams), (40 grams) and (50 grams). Data collection was carried out by observation method through organoleptic quality tests assessed by 30 panelists. Data from organoleptic tests with single anova or one away anova test and Duncan's follow-up test. To determine the content of proximate (protein, water content, fat, carbohydrates, ash) and β-carotene, laboratory tests were carried out. The results of the study showed: 1) the best proportion of mocaf flour wet noodles with the addition of the best yellow pumpkin puree from the organoleptic test was obtained from a sample of 350 with the addition of 50 grams of yellow pumpkin puree, with the characteristics of a slightly straight shape; dark yellow color; the taste is quite like yellow pumpkin; the chewy texture and aroma are quite flavorful of yellow pumpkin. 2) The nutritional content of the best wet noodle results with 350 samples based on laboratory tests shows that per 100 grams has a B-carotene content of 86.50 mg; water content of 48.10%; protein 4.90%; fat 4.25%; carbohydrates 3.90%; ash content of 1.18%.